Environmentally Benign Photocatalysts Applications of Titanium Oxide-based Materials - Anpo, Masakazu.; Kamat, Prashant V. (Nanostructure Science and Technology, 2010)
This book focuses on the various approaches used in the design and development of highly efficient, visible light responsive titanium oxide-based photocatalysts by applying such methods as sol-gel, precipitation, dip-coating, metal ion-implantation, and magnetron sputtering deposition. Titanium oxide-based photocatalysts and related catalysts are especially promising to investigate since they are stable, non-toxic, readily available, and highly efficient photofunctional materials. This book discusses the fundamental characterization studies carried out on the active sites and mechanisms behind photochemical reactions at the molecular level, as well as their potential applications. The book serves not only as a text for research into photochemistry and photocatalysis, but also explores the field of green technologies by experts in academia and industry. This book will appeal to those interested in research on the environmental impact of materials, catalysis, and photocatalysis.